Internalization Internalization of Tolerance Values through Akidah Akhlak Learning at MAN 1 Pringsewu and MA Darul Ulum - Mz, Riza Arif; Basri Basri; Ahmad Barizi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The lack of integration of tolerance and multiculturalism education has resulted in the continued prevalence of intolerant and radical attitudes among society and the younger generation.This study aims to describe the implementation and internalization process of tolerance values ​​through Akidah Akhlak learning at MAN 1 Pringsewu and MA Darul Ulum and to identify its impact on students' attitudes. The study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that MAN 1 Pringsewu emphasized cognitive and affective approaches in tolerance learning, such as through the delivery of material "Teenager Social Akhlak" and the screening of educational videos. Meanwhile, at MA Darul Ulum, the internalization process was carried out using a value classification approach, where students actively identified tolerant and intolerant attitudes through group discussions and the habituation of polite attitudes. The impact of the internalization of tolerance values ​​in both madrasas was seen in the increasing awareness of students to respect differences, maintain polite attitudes, and avoid deviant behavior both in and outside the school environment. This study emphasizes the importance of integrating tolerance values ​​in learning as a foundation for forming students' character amidst social diversity. Abstrak. Kurangnya integrasi pendidikan toleransi dan multikulturalisme menyebabkan masih maraknya sikap intoleran dan radikalisme di kalangan masyarakat dan generasi muda. Penelitian ini bertujuan untuk mendeskripsikan implementasi dan proses internalisasi nilai-nilai toleransi melalui pembelajaran Akidah Akhlak di MAN 1 Pringsewu dan MA Darul Ulum serta mengidentifikasi dampaknya terhadap sikap siswa. Penelitian menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa MAN 1 Pringsewu menekankan pendekatan kognitif dan afektif dalam pembelajaran toleransi, seperti melalui penyampaian materi “Akhlak Pergaulan Remaja” dan pemutaran video edukatif. Sementara itu, di MA Darul Ulum, proses internalisasi dilakukan dengan pendekatan klasifikasi nilai, di mana siswa aktif mengidentifikasi sikap toleran dan intoleran melalui diskusi kelompok dan pembiasaan sikap santun. Dampak dari internalisasi nilai toleransi di kedua madrasah tampak pada meningkatnya kesadaran siswa untuk menghargai perbedaan, menjaga sikap santun, serta menghindari perilaku menyimpang baik di lingkungan sekolah maupun di luar sekolah. Penelitian ini menegaskan pentingnya integrasi nilai-nilai toleransi dalam pembelajaran sebagai fondasi membentuk karakter peserta didik di tengah keberagaman sosial. Kata Kunci: Internalisasi, Nilai Toleransi, Akidah Akhlak, MAN 1 Pringsewu, MA Darul Ulum